Enhancing Student Participation and Understanding of Social Studies Material through the Implementation of the STAD Model: A Classroom Action Research at SMP Negeri 57 Muaro Jambi - Martono Martono; Dedi Hermon (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to improve student learning outcomes and activeness in Integrated Social Sciences (IPS) learning through the implementation of the Student Team Achievement Division (STAD) cooperative learning model in class VIII of SMP Negeri 57 Muaro Jambi. The research method used was Classroom Action Research (CAR). The research subjects were 25 class VIII students in the odd semester of the 2025/2026 academic year. Data were collected through observation, interviews, learning outcome tests, and documentation. The results showed that the implementation of the STAD model significantly improved student learning outcomes, with the average post-test score increasing from 66.52 in cycle I to 90.00 in cycle II. The percentage of learning completeness increased from 43% to 91.3%, while the N-Gain score increased from 0.23 (low category) to 0.67 (medium-high category). In addition, student learning activity and motivation also experienced a significant increase. Students became more active in thinking, dared to express opinions, and showed better cooperation and responsibility in groups. Thus, the application of the STAD-type cooperative model has proven effective in improving students' learning outcomes and social interactions in Integrated Social Studies learning at SMP Negeri 57 Muaro Jambi